Designing a Cloud Computing Marketing Strategy: A Case Study of Provider ABC, 2026–2028 - Kevin Stevanus Irwanto; Diah Nurul Hidayati (Indonesian Journal Publisher, 2026)
Rapid digital transformation has driven substantial growth in cloud computing adoption across emerging markets. In Indonesia, the cloud market is projected to expand at a CAGR of 14.32% from 2025 to 2031 (Mordor Intelligence, 2026). Despite this growth, marketing literature addressing how local cloud providers can compete against global hyperscalers in developing economies remains limited. This study aims to design an evidence-based marketing strategy for Provider ABC, a domestic cloud service provider in Jakarta, for the period 2026–2028, with the goal of achieving a revenue target of IDR 192 billion by end-2028. A descriptive qualitative approach was employed, utilising in-depth interviews with key internal stakeholders and systematic document analysis. The 4C framework (Context, Customer, Competitor, Company) guided the situational analysis, with findings synthesised into a 4P marketing mix strategy (Mullins & Walker, 2013; Kotler & Keller, 2016). The findings reveal that Provider ABC holds competitive advantages in 24/7 customer service, domestic data centre location, and transparent pricing, yet underperforms relative to global competitors in service-level agreements (SLA), compliance certifications, and digital marketing, yielding the lowest Competitive Profile Matrix score of 2.42 among evaluated rivals (David, 2011). The recommended strategies include: (1) targeting medium-to-large start-up companies as a new market segment, (2) developing Managed Cloud and Big Data as a Service offerings, and (3) intensifying digital promotion through SEO, Google Ads, and LinkedIn Ads. This study contributes a replicable strategic framework for local cloud providers competing in B2B emerging markets.